SEMANTIC MOVEMENT IN SOCIAL TIME AND POLYCHROMATIC PHENOMENA - Реймерс, Снежана (SWorldJournal, 2020)
Multicolored ness of natural occurrences reflects itself in the human consciousness, and helps a person find her way in the surrounding environment, adjust to its changes. Polychromatic phenomena (PCF) are artificially created color effects. Any material